From Creativity to Innovation: An Entrepreneur Strategic Management for Business Development - Mochamad Heru Riza Chakim; Fauzan Manafi Albar; Dahlia Pinem; Seprianti Eka Putri; Pandu Adi Cakranegara (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The purpose of this review was to understand creativity in driving business towards innovation, starting from improving management and business strategies that are profitable and sustainable. The authors believe that businesses have to transform management into a profitable business through innovation as an entrepreneur. So, to ensure the relevant supporting document data to answer the problems of this study, the authors have visited hundred of scientific publication journals, both national and international publications, which actively discuss issues of creativity, innovation, and business strategies to benefit both short and long term. Next, we examine the phenomenological approach under a descriptive qualitative study to understand genuinely. We found the data through an electronic search on several mentioned publications. Through the use of the keyboard, we have been able to collect data, and then we review it by coding the system, critical evaluation of the relevant conclusions. Based on the evidence of our studies and studies, we can finally conclude that entrepreneurs must have continuous creativity to get the latest innovations to compete in the era of economic competition by maximizing management governance, both production, and sales. In the end, we found that the business was going from creativity to innovation in developing profitable business management strategies. It is hoped that these findings will strengthen similar studies in the future.